Association of genomic variants at the human leukocyte antigen locus with cervical cancer risk, HPV status and gene expression levels. Issue 9 (10th July 2020) - Ramachandran, Dhanya; Schürmann, Peter; Mao, Qianqian; Wang, Yingying; Bretschneider, Lisa‐Marie; Speith, Lisa‐Marie; Hülse, Fabienne; Enßen, Julia; Bousset, Kristine; Jentschke, Matthias; Böhmer, Gerd; Strauß, Hans‐Georg; et al.
Abstract: The human leukocyte antigen ( HLA ) locus on chromosome 6 has been reported to be associated with cervical cancer. We investigated two independent single‐nucleotide polymorphisms in a large case‐control series of cervical dysplasia and carcinoma that has been newly established by the German Cervigen Consortium, comprising a total of 2481 cases and 1556 healthy females. We find significant associations for both variants, rs9272117 at HLA‐DQA1 and rs2844511 at MICA and HCP5, with cervical disease. Both variants showed evidence of association with invasive cervical cancer (rs9272117: OR 0.89, 95% CI 0.79‐0.99, P = .036; rs2844511: OR 1.17, 95% CI 1.04‐1.31, P = .008) and with high‐grade dysplasia (rs9272117: OR 0.78, 95% CI 0.70‐0.87, P = 7.1 × 10 −6 ; rs2844511: OR 1.13, 95% CI 1.01‐1.26, P = .035), as well as in a combined analysis of both groups (rs9272117: OR 0.83, 95% CI 0.75‐0.91, P = 6.9 × 10 −5 ; rs2844511: OR 1.14, 95% CI 1.04‐1.26, P = .005). Variant rs2844511, but not rs9272117, also showed modest evidence of association with low‐grade dysplasia (OR 1.26, 95% CI 1.04‐1.54, P = .019). In case‐only analyses, rs2844511 tended to predict HPV status ( P = .044) and rs9272117 tended to associate with HPV16 ( P = .022). RNA studies in cervical samples showed a significant correlation in the transcript levels of MICA, HCP5 and HLA‐DQA1, suggesting extensive co‐regulation. All three genes were upregulated in HPV16‐positive samples. In stratified analyses, rs9272117 was associated with HLA‐DQA1 levels, specifically in HPV‐positive samples, while rs2844511 was associated with MICA and HCP5 levels. The risk allele of rs2844511 was required for correlations between MICA or HCP5 with HLA‐DQA1 . Altogether, our results support 6p21.32‐33 as the first consistent cervical cancer susceptibility locus and provide evidence for a link between genetic risk variants, HPV16 status and transcript levels of HLA‐DQA1, HCP5 and MICA, which may contribute to tumor immune evasion. Abstract : What's new? The HLA locus, on chromosome 6, appears to contribute to cervical cancer risk, according to some studies. Genome wide association studies have uncovered two candidate variants on that chromosome: rs2844511, at the HLA‐DQ1 gene, and rs9272117, located in an intron of lncRNA HCP5, downstream of the MICA gene. Here, the authors tested the contribution of the two variants through genotyping of 2500 cervical cancer cases and 1500 healthy controls. Both variants showed an association with cervical cancer and with high‐grade dysplasia, and they modulated the expression levels of nearby genes in cervical cells, providing evidence for the first cervical cancer susceptibility locus.